The Effect of Lemon Skin Extract on Uric Acid Levels of Hyperuricemia Male Wistar Rats - Revi Ardiansyah; Noor Wijayahadi; Endang Mahati; Yora Nindita (Jurnal Kedokteran Diponegoro, 2024)
Background: Purine metabolism, carried out in the liver, results in the production of uric acid. Hyperuricemia is a condition of elevated level of uric acid in the blood that can lead to gout if untreated. Lemon (Citrus Limon.) contains flavonoids which act as antioxidants and have the potential role as antihyperuricemia. Aim: To determine the effect of lemon peel extract on uric acid levels. Methods: Thirty-six male wistar rats from Farmhouse Ungaran were randomly divided into 6 groups, consists of healthy control group (K0), hyperuricemic control (K1), allopurinol control (K2), and 3 treatment groups (P1, P2, P3). Hyperuricemia induced with administration of block broth and potassium oxonate for 4 weeks. Lemon peel extract doses of 17,5, 35, and 70 mg/kg BW, and allopurinol 90 mg/kg BW was given orally for 2 weeks. Statistical analysis was conducted to evaluate differences among groups before and after the intervention. Results: There was a significant difference (p<0,05) in uric acid levels before and after intervention of lemon peel extract in groups K1, K2, and P3. Meanwhile, in groups K0, P1, and P2, there were no significant differences observed. In the pre-test uric acid levels, there was a significant difference (p<0,05) between the K0 group and K1, K2, P1, P2, and P3. Conclusion: There were no significant differences observed in the uric level acid of the treatment and control group after intervention, but there were significant differences in the effects of graded dosages between the treatment groups.